Recontextualization practices: A scale of directness - Weizman, Elda (Frontiers in Communication, 2023)
I analyze Israel president Rivlin's 2020 speech delivered against the background of ongoing Covid-19 health threats and a severe political crisis, and its follow-ups in online news articles and in ordinary readers' comments on relevant news sites and on Facebook. I examine the recontextualization practices used in this three-part discourse event, shedding light on their diversity and focusing on the degree of directness they manifest. It shows that the president recontextualizes the complex political and social crisis through the lens of the Covid-19 pandemic. He frames the pandemic in terms of its morbid, mythic and moral dimensions, as well as its influence on various aspects of civil and political disorder. This connection is drawn through the juxtaposition of propositions and the shifts between the deliberative and the epidictic keyings. alluding to Jewish tradition, prayers and blessings. Through the use of the inclusive "we", he self positions as a leader on a par with ordinary people, whereas through direct demands formulated in the plural without personal naming he addresses his ratified addressees, the MPs and the ministers, and thus self-positions as an authority demanding accountability from the current leadership. The news articles in leading online media are short and partial, recontextualizing the speech and the situation through their titles, the selection of the extracts they chose to present and the very few evaluations they make. They mostly take up the president's moral framing and some of his explicit demands for political accountability. The commenters mostly follow up on the moral framing and the mythic dimensions proposed by the president but offer a different perspective on these issues. They shift the responsibility for "losing the compass" from the collective "we" advocated by the president to the politicians including the president, and they ironically echo the epidictic keying in order to challenge and even ridicule it. They further add another dimension to the speech event, by framing the president's speech as politically biased. The discursive patterns used all along this thread of discourses by all its participants range in degree of directness and recontextualize the object of talk, perspectives, keying and positionings.